2017
DOI: 10.7717/peerj.3471
|View full text |Cite
|
Sign up to set email alerts
|

LuxS-dependent AI-2 production is not involved in global regulation of natural product biosynthesis inPhotorhabdusandXenorhabdus

Abstract: The Gram-negative bacteria Photorhabdus and Xenorhabdus are known to produce a variety of different natural products (NP). These compounds play different roles since the bacteria live in symbiosis with nematodes and are pathogenic to insect larvae in the soil. Thus, a fine tuned regulatory system controlling NP biosynthesis is indispensable. Global regulators such as Hfq, Lrp, LeuO and HexA have been shown to influence NP production of Photorhabdus and Xenorhabdus. Additionally, photopyrones as quorum sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(94 reference statements)
1
2
0
Order By: Relevance
“…The quorum in this case activates a signaling cascade that transcribes the operon responsible for the Photorhabdus clumping factor (Pcf)a biofilm-like phenotype that plays a vital role in the pathogenicity of these bacteria. 14,16,17 These findings encompass the first demonstration of 2-pyrones, specifically 3-alkyl-4-hydroxy-6-isobutyl-2H-pyran-2-ones (Figure 1), acting as signaling molecules in any bacterial strain. Although the findings specified the detection of endogenously produced PPY signals, it is also known that orphan receptors can be used to respond to exogenous signals, produced by coinhabiting microorganisms, for example.…”
Section: ■ Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The quorum in this case activates a signaling cascade that transcribes the operon responsible for the Photorhabdus clumping factor (Pcf)a biofilm-like phenotype that plays a vital role in the pathogenicity of these bacteria. 14,16,17 These findings encompass the first demonstration of 2-pyrones, specifically 3-alkyl-4-hydroxy-6-isobutyl-2H-pyran-2-ones (Figure 1), acting as signaling molecules in any bacterial strain. Although the findings specified the detection of endogenously produced PPY signals, it is also known that orphan receptors can be used to respond to exogenous signals, produced by coinhabiting microorganisms, for example.…”
Section: ■ Introductionsupporting
confidence: 52%
“…Although not fully understood, systems lacking any LuxI-like AHL synthase can still encompass proteins with homology to LuxR-type receptors, namely LuxR orphans or solos. , Seminal reports by Heermann and co-workers explicitly target the concept that non-AHL producing bacteria can employ these receptors in the detection of other endogenously synthesized compounds and operate a QS signaling pathway. , Critically, this group unearthed “photopyrones” (PPYs) participating in the QS network of the Gram-negative pathogen Photorhabdus luminescens through an orphan LuxR receptor. The quorum in this case activates a signaling cascade that transcribes the operon responsible for the Photorhabdus clumping factor (Pcf)a biofilm-like phenotype that plays a vital role in the pathogenicity of these bacteria. ,, These findings encompass the first demonstration of 2-pyrones, specifically 3-alkyl-4-hydroxy-6-isobutyl-2 H -pyran-2-ones (Figure ), acting as signaling molecules in any bacterial strain …”
Section: Introductionmentioning
confidence: 96%
“…Recently, a metabolomic‐based study in E. coli confirmed that TolC‐dependent pumps play an important role in cell metabolism by demonstrating that AcrAB pump deletion or overproduction was associated with changes in a large number of central metabolism intermediates (Cauilan et al ., 2019). Therefore, the accumulation of such metabolites and compounds in AcrAB mutants could be toxic or at least disadvantageous at a given moment in Photorhabdus life cycle, producing a negative feedback on the production of attributes directly or indirectly required to infect and colonize the host as shown in Salmonella Typhimurium (Webber et al ., 2009; Heinrich et al ., 2017). In harmony with this, the slight virulence exaltation noted upon acrAB overexpression in mutant strains is suggestive of an enhanced production/export of yet unknown bacterial effectors/toxic compounds via the AcrAB pump, contributing to a better adaptation and survival to the complex stresses within the dying insect.…”
Section: Resultsmentioning
confidence: 99%